The detection of circulating plasma cells may improve the Revised International Staging System (R‐ISS) risk stratification of patients with newly diagnosed multiple myeloma. (1st April 2021) - Galieni, Piero; Travaglini, Fosco; Vagnoni, Davide; Ruggieri, Miriana; Caraffa, Patrizia; Bigazzi, Catia; Falcioni, Sadia; Picardi, Paola; Mazzotta, Serena; Troiani, Emanuela; Dalsass, Alessia; Mestichelli, Francesca; et al.
Summary: The Revised International Staging System (R‐ISS) stratifies patients affected by Multiple Myeloma (MM) into three distinct risk groups: R‐ISS I [ISS Stage I, Standard‐Risk cytogenetics and normal Lactase DeHydrogenase (LDH)], R‐ISS III (ISS stage III and either high‐risk cytogenetics or high LDH) and R‐ISS II (any other characteristics). With the aim to verify whether the three R‐ISS groups could be divided into subgroups with different prognostic factors based on the detection of Circulating Plasma Cells (CPCs) at diagnosis, in this retrospective analysis, we evaluated 161 patients with MM treated at our centre between 2005 and 2017. In all, 57 patients (33·9%) were staged as R‐ISS III, 98 (58·3%) as R‐ISS II and six (3·6%) as R‐ISS I. CPCs were detected in 125 patients (74·4%), while in 43 patients (25·6%) no CPCs were seen. Our analysis revealed that Overall Survival (OS) and progression‐free survival (PFS) rates in R‐ISS II patients were higher in the subgroup without CPCs compared to the subgroup with ≥1 CPCs (OS: 44·7% vs. 16·3%, P = 0·0089; PFS: 27·8% vs. 8·1%, P = 0·0118). Our present findings suggest that the detection of CPCs at diagnosis may be used as a further prognostic biomarker to improve the risk stratification of patients with MM staged as R‐ISS II.